TheSocialMedwork: providing access to overseas medicines. Issue 2 (20th February 2019) - Ogden, Joy
Abstract : TheSocialMedwork is an online service that helps patients across the world to access new medicines that are not approved in their own country. Joy Ogden talks to its founder and CEO Sjaak Vink about the service's achievements, obstacles and long‐term goals.